Developing identity in diversity: a second language acquisition experience - Hamidah Yamat, (Penerbit UKM, 2012)
This paper discusses how three young Malaysian children aged six developed an identity while experiencing second language acquisition (SLA). It illustrates how language difference which is an aspect of diversity has lead learners to develop an identity as language learners. The discussion is based on the findings of an ethnographic case study on three young Malaysian children’s SLA experiences in the United Kingdom (U.K). The aim of this study is to gather insights from these children about their SLA experiences while attending a mainstream school and living in the U.K. This is to enhance our understanding about the process. The children were interviewed as individuals and as a group; and were observed at school and home. Transcripts of the interviews and observations were examined closely to identify themes for analysis and discussion. The findings indicate that the children experienced SLA as a socialization process in which the target language was being used to get on with life in a mainstream classroom and at home. The findings indicated several factors that might have an impact on the children’s SLA. One that had a significant impact was that the children, without their awareness, were developing an identity in dealing with diversity.